2018
DOI: 10.1007/s12185-018-2518-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic transcriptional program driven by TAL1 in T-cell acute lymphoblastic leukemia

Abstract: TAL1/SCL is a prime example of an oncogenic transcription factor that is abnormally expressed in acute leukemia due to the replacement of regulator elements. This gene has also been recognized as an essential regulator of hematopoiesis. TAL1 expression is strictly regulated in a lineage- and stage-specific manner. Such precise control is crucial for the switching of the transcriptional program. The misexpression of TAL1 in immature thymocytes leads to a widespread series of orchestrated downstream events that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 141 publications
(216 reference statements)
0
26
0
1
Order By: Relevance
“…For example, the genetic looping interactions are known to be associated with the expression of ARID5B (Studd et al, 2017). ARID5B may serve as a transcriptional activator that enhances the regulatory network triggered by the TAL1 complex in T-ALL cell proliferation (Tan, Zhang & Sanda, 2019). In recent years, studies showed that the mutations and single nucleotide polymorphisms of TF, ARID5B are involved in the oncogenesis of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the genetic looping interactions are known to be associated with the expression of ARID5B (Studd et al, 2017). ARID5B may serve as a transcriptional activator that enhances the regulatory network triggered by the TAL1 complex in T-ALL cell proliferation (Tan, Zhang & Sanda, 2019). In recent years, studies showed that the mutations and single nucleotide polymorphisms of TF, ARID5B are involved in the oncogenesis of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The TAL1 gene is an essential transcriptional regulator of hematopoiesis, in particular for the specification of hematopoietic lineages [39]. TAL1 is also implicated as a key transcriptional factor involved in the development of T-cell acute lymphoblastic leukemia [40]. Similarly, the MLLT3 (mixed lineage leukemia, translocated to 3, also known as AF9) gene is a critical regulator of hematopoietic stem cell self-renewal, and also implicated in leukemias [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…TAL1/SCL is considered as a master TF delineating the cell fate and the identity of progenitor and normal hematopoietic stem cells (HSCs). It regulates other hematopoietic TFs thus has a potential for cell reprogramming [22]. TAL1 also binds CBP/p300 acetyltransferase [61,62].…”
Section: The Role Of the Bhlh Proteins In Transcriptionmentioning
confidence: 99%